(untitled) (KULT_online, 2019)
Since the late 1990s European and international organizations have been dealing with the remembrance of the holocaust as the main national-socialist crime against humanity. Using the example of the Strasbourg-based Council of Europe, Elisabeth Kübler emphasizes context and content of the supranational work regarding this crime. She focuses thereby on the implementation of a politics of holocaust memory in a cosmopolitan Europe.